The Contextualization of The Teachings of Islamic Law in The Legal World in Indonesia - Muhammadong (Eastasouth Institute, 2023)
The purpose of this research is to find out the contextualization of the teachings of Islamic law within the framework of legal politics in Indonesia. The existence of Islamic law did not only apply during the colonial period but could exist in the national legal system. The contribution of Islamic law is very large for the progress of the development of Islamic teachings in Indonesia. Birth of Law No. I of 1974 concerning Marriage, Law No.7 of 1989 concerning Religious Courts. The Compilation of Islamic Law (KHI), and PP No. 28 of 1978 concerning waqf, show that Islamic law is a teaching in the legal system in Indonesia. Islamic law is believed to be a teaching that can bring about changes in the way of life of Muslims.